Human Resources Development Policy as a Strategy for Improving Public Organizational Performance - Eka Sunahwati; Muhammad Syamsul Maarif; Anggraini Sukmawati (Magister Administrasi Publik, 2019)
The purpose of this research was to analyze organizational performance improvement strategies in the Center for Testing the Implementation of New Fisheries Products (BBP2HP). The research was conducted using AHP (Analytical Hierarchy Process) method with Expert Choice software to analyze the structure and the main strategy alternatives. The analysis was based on primary data obtained through interviews with 11 experts. Research results showed that human resource development policy was the most crucial strategy in improving BBP2HP organizational performance with training and development as an integral part of the strategy. The results also showed that the factor of leadership was of most importance in ensuring that the strategy of improving organizational performance. In that regard, leadership qualities of BBP2HP head was identified as the most critical and influential actor in improving BBP2HP organizational performance Meanwhile, providing excellent services was identified as the top priority that BBP2HP must pursue in improving its organizational performance as public service unit. The implications of this study are public organizations should implement training and development in accordance with the needs of the organization; and the pivotal role that leadership plays in the strategic management of the organization in empowering and directing organizational resources towards achieving organizational goals in as effective and efficient a manner.